Atmospheric Visibility and Angström Exponent Measurements through Digital Photography - Carretas, Filipe (2016)
This paper presents a low-cost system for the measurement of atmospheric visibility. The measurement setup is composed by a consumer digital camera which is controlled by a computer. The camera acquires photos of the landscape that include natural dark objects. Then the computer calculates the atmospheric visibility based on the apparent contrast, against the background, of these dark objects through the Lambert–Beer law. Two different approaches are proposed so that the system is able to measure the atmospheric visibility both under normal and low visibility conditions. The use of the three color channels of the camera allows the measurement of the extinction coefficient at different wavelengths along with the Angström exponent which is an important parameter in the classification of atmosphere aerosols. Measurements performed with the developed system are presented and include the atmospheric visibility, the extinction coefficient and the Angström exponent. The results presented correspond to the measurements performed along a week that included a desert dust event. This event dramatically reduced the atmospheric visibility due to the desert dust particles. Angström exponent measurements were performed with another instrument for comparison. Finally, an uncertainty analysis of the measured atmospheric visibility is presented.